Linking intravenous drug users to treatment through non-governmental organizations in Ukraine: how well is it working? - Kuznetsova, Julia; Sereda, Yulia; Denisiuk, Olga; Kravchenko, Nataliia; Jayaraj, Joshua; Smyrnov, Pavlo; Mykhalchuk, Tetiana; Zachariah, Rony (The Journal of Infection in Developing Countries, 2019)
Introduction: Alliance for Public Health, the International Charitable Foundation, coordinates HIV prevention in Non-Governmental Organizations (NGO) working with people who inject drugs (PWID) in Ukraine. We aimed to describe the performance of the differential model of linking PWID to HIV care and treatment (Community Initiated Treatment Intervention – CITI). Methodology: A retrospective cohort study using routine program data was conducted among 8,927 PWID who were tested positive for the first time during January 2016 – June 2017. Study outcomes were enrollment into CITI and initiating antiretroviral treatment (ART). Factors associated with outcomes were estimated by logistic regressions with random effects. Results: Among the study participants, 54% enrolled into CITI and 23% initiated ART. CITI enrolment was associated with being married (adjusted odds ratio (AOR) = 1.17; 95%: 1.02-1.34); less than weekly compared to daily (AOR = 1.31; 95%: 1.13-1.52); less than 5 years of drug use compared to > 14 years (AOR = 1.73; 95%: 1.40-2.13), and having no criminal records (AOR = 1.30; 95%: 1.12-1.50). Factors of non-ART initiation were male gender (AOR = 1.33; 95%: 1.16-1.53); being single (AOR = 1.48; 95%: 1.21-1.82); drug use duration > 14 years compared to < 5 years (AOR = 1.38; 95%: 1.03-1.85), unemployment (AOR = 1.45; 95%: 1.15-1.83) and history of incarceration (AOR = 1.21; 95%: 1.003-1.45). Conclusion: Mobilizing the NGO community and PWID to engage in outreach HIV testing activity and harm reduction for key populations has succeeded in opening the gateway to prevention, care and ART for thousands of PWID in Ukraine.